Determination of dimethoate, lambda-cyhalothrin and malathion residues in guava fruits using GCMS-tandem mass spectrometry - Devi, Meenakshi; Duhan, Anil; Kumari, Beena; Yadav, G.S. (Indian Journal of Horticulture, 2016)
Tephritidae fruit flies are considered key insect pest in guava which cause yield loss and degradation of quality. A trial was conducted in guava orchard during 2013 to study residue dissipation rate of two organophosphates, dimethoate and malathion and one synthetic pyrethroid insecticide, lambda-cyhalothrin. The insecticides were applied at recommended and double of the recommended dose on semi-ripe guava fruits. The fruits were randomly sampled at different time intervals, i.e. 0 (2 h), 3, 7 and 10 days after spray. After extraction and clean-up, the residues were estimated using GCMS tandem mass spectrometry. The half-life values at single and double dose applications were found to be 6.72 and 8.15 days for dimethoate, 4.41 and 4.71 days for lambda-cyhalothrin and 3 and 3.3 days for malathion. The residues reached below maximum residue limit (MRL) on zero day following recommended dose application of all insecticides. In double dose application, residues reached below MRL on zero day in malathion and lambda-cyhalothrin and on 3rd day in dimethoate. Washing of guava fruits removed 42.9 and 45.2% dimethoate, 33 and 36.8% lambda-cyhalothrin, 50 and 54.5% malathion residues at single and double dose applications in 0 day samples. Lambda-cyhalothrin was found most effective followed by dimethoate and malathion for controlling fruit fly in guava.